Misogyny, misandry, and misanthropy - Bloch, R. Howard; Ferguson, Frances (Online access: California Digital Library UC Press E-Books Collection, 1982-2004 (Open Access), 1989)
These essays, originally comprising an issue of Representations, explore the relation between gender, eroticism, and violence through close analysis of a range of both high and popular cultural forms, from R. Howard Bloch on medieval theology to Carol Clover on contemporary slasher films. Does misogyny differ from misandry? Can author intention be separated from social context? Do good women counterbalance or reenforce the misogyny of negative examples? Is an obsession with women itself misogynistic? These questions are approached from various angles by Joel Fineman, Charles Bernheimer, Jacqueline Lichtenstein, Frances Ferguson, Naomi Schor and Gillian Brown. In sum, the authors detail not only the ways in which gender is represented, but also the changes to which representation subjects questions of sexual difference. Publisher's description.